Arbitration and mediation as a mechanism to settle corporate dispute in Bangladesh - Rashid, Md Mamonor (2016)
This study examines the mechanism of arbitration and mediation to settle corporate disputes in Bangladesh. This study intends to create awareness among the Bangladeshi corporations of the importance of addressing arbitration and mediation to settle corporate disputes. Currently there are around 2.3 million backlog of cases pending in the courts of Bangladesh. It is extremely crucial to clear off these backlog of cases, but so far the courts are unable to provide a satisfactory settlement of the cases, causing endless suffering to the litigants. The objective of this study is to examine the role of arbitration and mediation in providing alternative mechanisms to settle corporate disputes in Bangladesh. This study analyses the provisions of laws specially the Arbitration Act 2001, and the Code of Civil Procedure 1908 regarding arbitration and mediation in Bangladesh. The data of this study was analyzed through the historical, analytical, philosophical and comparative approaches. The findings show that the arbitration and mediation mechanisms provide the following positive characteristics: quicker, convenient, confidential, less procedural, cost effective and enforceable by the court; on the other hand, extensive delay, huge costs, harassment of the parties and the huge backlog of cases that could lead corporate or commercial parties not to go to the courts were negative. The study concludes that the use of the arbitration and mediation mechanisms is the preferred way to settle corporate or commercial disputes in Bangladesh. However, implementation of the arbitration and mediation mechanisms to settle corporate disputes in Bangladesh can only be successful if there is sufficient government support and regulation, professional ethics, relevant training and facilities.